Characterizing facial features in individuals with craniofacial microsomia: A systematic approach for clinical research. Issue 11 (November 2016) - Heike, Carrie L.; Wallace, Erin; Speltz, Matthew L.; Siebold, Babette; Werler, Martha M.; Hing, Anne V.; Birgfeld, Craig B.; Collett, Brent R.; Leroux, Brian G.; Luquetti, Daniela V.
Abstract : Background: Craniofacial microsomia (CFM) is a congenital condition with wide phenotypic variability, including hypoplasia of the mandible and external ear. We assembled a cohort of children with facial features within the CFM spectrum and children without known craniofacial anomalies. We sought to develop a standardized approach to assess and describe the facial characteristics of the study cohort, using multiple sources of information gathered over the course of this longitudinal study and to create case subgroups with shared phenotypic features. Methods: Participants were enrolled between 1996 and 2002. We classified the facial phenotype from photographs, ratings using a modified version of theO rbital, E ar, M andible, N erve, S oft tissue (OMENS) pictorial system, data from medical record abstraction, and health history questionnaires. Results: The participant sample included 142 cases and 290 controls. The average age was 13.5 years (standard deviation, 1.3 years; range, 11.1–17.1 years). Sixty‐one percent of cases were male, 74% were white non‐Hispanic. Among cases, the most common features were microtia (66%) and mandibular hypoplasia (50%). Case subgroups with meaningful group definitions included: (1) microtia without other CFM‐related features ( n = 24), (2) microtia with mandibular hypoplasia ( n = 46), (3) other combinations of CFM‐ related facial features ( n = 51), and (4) atypical features ( n = 21). Conclusion: We developed a standardized approach for integrating multiple data sources to phenotype individuals with CFM, and created subgroups based on clinically‐meaningful, shared characteristics. We hope that this system can be used to explore associations between phenotype and clinical outcomes of children with CFM and to identify the etiology of CFM. Birth Defects Research (Part A) 106:915–926, 2016.© 2016 Wiley Periodicals, Inc.